The pragmatic translator : an integral theory of translation - Morini, Massimiliano (Bloomsbury advances in translation., 2013)
This book is concerned with translation theory. It proposes an all-round view of translation in the terms of modern pragmatics, as articulated in three pragmatic functions (performative, interpersonal and locative) which describe how translated texts function in the world, involve readers and are rooted in their spatio-temporal contexts. It presents a full and up to date view of translation that takes into account thirty years of research in the field of Descriptive Translation Studies. Unlike DTS, the theory provides an account of products and processes. This publication exhibits the need for.